The mineralogy of the Ågskardet lithium pegmatite at Meløy in Nordland, Norway - Caixeta Borges, Patricia (2023)
The Ågskardet lithium pegmatite, part of the Meløy-Gomfjord pegmatite field in Nordland, is emplaced in the Caledonian Rödingsfjället nappe complex between two tectonic windows exposing Svecofennian granite gneisses. It represents one of the few pegmatites in Norway with chemical Li-Cs-Ta affinity. Because of the current high industrial demand for Li, research on Li pegmatites is of utmost importance to understand the origin, genesis and Li-enrichment processes of these rocks. The pegmatite body is exposed in small open pits and forms a lenticular-shaped body of approximately 30 x 150 m oriented in WSW-ENE direction. Different zones within the pegmatite are identified through mineralogical and textural changes, mapped as wall zone, at the contact with the host rocks, followed by an intermediate zone and the core. Closest to the central part, numerous irregular, fine-grained albite replacement zones occur discordant across the intermediate zone and core. The albite replacement zones represent the most evolved parts of the pegmatite with unique mineralogy reflecting an enrichment of incompatible elements including Li, Rb, Cs, Ta, Tl, W, Sn, F, Nb, Mn, and Bi. To characterize the mineralogy and understand the pegmatite’s zoning and crystallization evolution, tourmaline, mica, and apatite were sampled from the different zones and analysed using electron probe microanalysis (EPMA), laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS) and scanning electron microscopy (SEM). Optical microscopy was used to identify inclusions and internal textural variations in these minerals. In addition, results of whole-rock analysis were compared to identify the genetic relationships between them. A crystallization sequence of the Ågskardet pegmatite is proposed. Element analysis of mica and tourmaline revealed an enrichment of compatible elements, manifested by the formation of liddicoatite and zinnwaldite during the final crystallization stage contradicting the expected continuous fractionation trend. A possible ...